2011
DOI: 10.1088/0031-8949/2011/t145/014036
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of grain boundary diffusion of hydrogen in tungsten

Abstract: Abstract. Understanding the influence of the microstructure of tungsten on hydrogen transport is crucial for the use of tungsten as first-wall material in fusion reactors. Here we report results from molecular dynamics and transition state studies on the influence of grain boundaries in tungsten on the transport of hydrogen. An exhaustive mapping of possible minimum activation energy migration trajectories for hydrogen as trace impurity reveals a strongly modified activation energy distribution in the neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…Light species in CGW tend to nucleate in vacancy clusters forming overpressurized bubbles that lead, among other effects, to surface blistering and exfoliation [8][9][10]. In view of this, the light species behaviour in W has been experimentally studied [11][12][13][14][15] and modelled [16,17] by many groups all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Light species in CGW tend to nucleate in vacancy clusters forming overpressurized bubbles that lead, among other effects, to surface blistering and exfoliation [8][9][10]. In view of this, the light species behaviour in W has been experimentally studied [11][12][13][14][15] and modelled [16,17] by many groups all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore plausible that some of the oxygen could react with the hydrogen, forming water, which would easily be removed from the system. The bond energy of Si-O bonds in SiO2 is approximately 6.44 eV / atom [17], a relatively low value which could easily be overcome by high kinetic energy particles. Also important to note, the Si-Si metallic bond energy is 3.38 eV per atom [17].…”
Section: Macormentioning
confidence: 99%
“…The bond energy of Si-O bonds in SiO2 is approximately 6.44 eV / atom [17], a relatively low value which could easily be overcome by high kinetic energy particles. Also important to note, the Si-Si metallic bond energy is 3.38 eV per atom [17]. As a brief but important aside, the bond energies of MgO, K2O, and Al2O3 are much higher than that of the Si-O bond.…”
Section: Macormentioning
confidence: 99%
“…For pure tungsten, a very recent review [49] mostly based on laboratory experiments [50,51,52] has shown, that the hydrogen retention will not cause a challenge in ITER even when taking into account effects of radiation damage [53,54]. It has to be stated however that the possible influence of increased H diffusion along grain boundaries as modelled in [55] is not yet taken into account. During the transition of ASDEX Upgrade (AUG) from graphite to tungsten, a reduction of the deuterium retention by almost a factor of ten has been observed.…”
Section: Hydrogen Retentionmentioning
confidence: 99%